A vision of compassion fatigue in palliative care - Castillo-Cáceres, Diana Jessica (2022)
Palliative care (PC) improves the quality of life of patients, caregivers and their families when they face physical, psychological, social or spiritual problems inherent to a life-threatening illness. The CP team provides comprehensive management, trying to minimize suffering in all dimensions; which carries a high emotional charge; experiencing compassion on a very individual basis, either as compassion satisfaction (CS) or compassion fatigue (CF). CF is a complex process, it includes the deterioration of personal resources, affecting professional and personal areas. CF must be addressed in a conscious way, increase its recognition and minimize its impact since this improves decision-making, clarity of communication and patient, family, caregiver and health professional satisfaction.